LECTURERS’ FEEDBACK ON WHATSAPP GROUP: STUDENTS’ PERCEPTION DURING ONLINE CLASS - Yustina Fitriani; Murti Bandung (INOVISH JOURNAL, 2021)
Abstract: This research is aimed to know the students’ responses to the feedback given by the lecturers during online class and to know the students’ motivation after feedback given. This research belongs to descriptive qualitative. Sampling technique used was purposive sampling. The participants were students of the second semester who takes an English major in Samarinda. The results showed that students felt happy with the feedback given by lecturers toward the learning materials. They can identify their mistakes, so they can correct them immediately and will not repeat the same mistakes. The students also appreciate it because it really helps them as students to be better in the future. In addition, the feedback given also can improve students’ motivation. They become more enthusiastic to learn more.Keywords: feedbacks, perception, online learning